Purposefulness and spontaneity as properties of self-organization of thinking - Denis F. Dautov; Alla K. Belousova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper describes thinking as a complex self-organizing system that simultaneously demonstrates such properties as spontaneity and purposefulness. Such an idea of thinking allows us to consider the specific components of thinking involved in its self-organization when processing arrays of information. This is of particular interest for improving tactical and strategic training methods. The main theories of self-organization are described and analyzed. Among the presented theories devoted to the problem of self-organization, special attention is paid to the theory of complex thinking and the theory of autopoiesis, the cybernetic and synergetic approach, the theory of dissipative structures. The description of thinking and related phenomena was based on the theory of cognitive structures, mental models and the theory of double coding. The features characteristic of theories postulating the spontaneous or purposeful nature of complex self-organizing systems are generalized. It is proposed to use a number of general provisions of self-organization theories to describe the processes and structures of thinking. Attention is drawn to the role of verbal and nonverbal components of thinking in its self-organization when working with information. The features of processing symbolic and figurative information at the verbal and non-verbal level are considered. Attention is drawn to the correlation of the conscious and unconscious in the human psyche, with the manifestations of verbal and nonverbal components of thinking. An assumption is made about the features of information processing of the verbal and nonverbal components of thinking. The analysis of their connection with the conscious and unconscious areas of the psyche is carried out. The possible procedural and structural aspects of self-organization of thinking, implemented on the basis of verbal and nonverbal thinking, are determined. The assumption is made about the use of the obtained results in training to improve the efficiency of information assimilation.